Antibiotic use in the treatment of diabetic foot ulcers: A cross-sectional study at a general hospital, Vietnam in 2023 - 2024 - Hue, Vu Thi; Hoan, Ngo Dang; Linh, Nguyen Van; Chi, Nguyen Pham Quynh; Duong, Huynh Hai; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Diabetic foot ulcers (DFUs) are a frequent diabetes complication, creating major social, psychological, and economic burdens. With rising antibiotic resistance and the high prevalence of infected DFUs, rational and safe antibiotic use is increasingly important. Objectives: This study investigated the prevalence and patterns of antibiotic use and evaluated the appropriateness and safety of therapy for infected DFUs at Thong Nhat Dong Nai General Hospital. Materials and methods: A cross-sectional, retrospective study was conducted from June 2023 to December 2024. Medical records of 235 patients aged ≥ 18 years with infected DFUs were reviewed. Data included patient characteristics, antibiotic regimens, and outcomes. Appropriateness and safety were assessed using international and national guidelines. Results: Among 235 patients (mean age 60.71 ± 12.28 years; male-to-female ratio 1:1.06), vancomycin was most frequently used prior to antimicrobial susceptibility testing (AST) (42.13%), while piperacillin/tazobactam was most frequently used following AST (77.10%). Most patients continued empirical therapy (65.53%). Dose and regimen appropriateness were 68.94% and 66.53%. Adverse reactions included gastrointestinal disturbances (7.65%), allergies (5.11%), and neurological effects (0.85%). Drug-drug interactions were frequent: moderate 53 - 62% and severe 9 - 15%. Conclusion: Antibiotic prescribing was generally guideline-consistent but associated with adverse reactions and moderate-to-high interaction risks, highlighting the need for careful monitoring and enhanced clinical pharmacy support.